The media and financial crises : comparative and historical perspectives - Schifferes, Steve; Roberts, Richard (Routledge, 2015)
"The Media and Financial Crises provides unique insights into the debate on the role of the media in the global financial crisis. Coverage is inter-disciplinary, with contributions from media studies, political economy and journalists themselves. It features a wide range of countries, including the USA, UK, Ireland, Greece, Spain and Australia, and a completely new history of financial crises in the British press over 150 years. Editors Steve Schifferes and Richard Roberts have assembled an expert set of contributors, including Joseph E Stiglitz and Lionel Barber, editor of the Financial Times. The role of the media has been central in shaping our response to the financial crisis. Examining its performance in comparative and historical perspectives is crucial to ensuring that the media does a better job next time.The book has five distinct parts:The Banking Crisis and the MediaThe Euro-Crisis and the MediaChallenges for the MediaThe Lessons of HistoryMedia Messengers Under InterrogationThe Media and Financial Crises offers broad and coherent coverage, making it ideal for both students and scholars of financial journalism, journalism studies, media studies, and media and economic history"--